Comparative diagnostic imaging in giant African land snails (Achatinidae) - Gumpenberger, Michaela; Schmidt-Ukaj, Silvana; Handschuh, Stephan (Frontiers in Veterinary Science, 2023)
Giant African land snails (GALS) have become increasingly popular, for example, as pets or in kindergartens in Europe, but little is known about their clinically relevant anatomy, diseases, or further details in diagnostic imaging. The present study focuses on the techniques and image interpretation of radiography, computed tomography, and sonography in GALS. The aim of the study is to find the most appropriate imaging tool to visualize the various organs within the mantle cavity (also known as visceral mass) in GALS. The detailed anatomy of GALS is presented with numerous figures of the different imaging techniques. The sensory organs and nervous system will not be part of the present study.